The effects of omega-3 fatty acid supplementation on serum myostatin, body composition, blood glucose, lipid profile and hs-CRP level in overweight men with coronary heart disease: A randomized double-blind placebo controlled clinical trial - Mohammad sharifzadeh; Leila setayesh; Mohammad Reza Emami; Shirin Jafari Salim; Mo hammad Hassan Javanbakht (Human Nutrition & Metabolism, 2024)
Background: Cardiovascular diseases, including heart cachexia, are considered as one of the most critical issues in health care that could be affected by several factors, such as myostatin whose critical role has been confirmed in the progress of heart cachexia and cardiac muscle dysfunction. This study was conducted to clarify the precise role of omega-3 polyunsaturated fatty acid (ω-3PUFA) on lipid profile, blood glucose, body composition, and serum level of myostatin in individuals with coronary artery disease (CAD). Materials and methods: Forty-two adult males (aged 45–65 years) with CAD had been confirmed by angiography were randomly divided into two groups, group 1 received omega-3 (1200mg daily) and group 2 received placebo (paraffin) for 8 weeks. The serum level of myostatin was measured using an ELISA kit in the beginning and at the end of the intervention. Moreover, body composition and anthropometric measurements of the patients were also evaluated. Result: A significant difference was observed in the myostatin level after 8weeks of intervention with omega3 supplement between omega3 and placebo group (p = 0.02).There was a significant difference in high-sensitivity C-reactive protein(hsCRP) concentration (p = 0.02) and low-density lipoprotein cholesterol (p = 0.01) between intervention group and control group at the end of the intervention. However, no statistically significant changes were seen in the body composition, anthropometric parameters, fasting insulin level, and fasting blood sugar within and between the groups. Conclusion: Omega-3 oral supplementation may improve the status of CAD patients by decreasing the level of myostatin, LDL-C and hs-CRP.